De Ticuna a Magüta um estudo sobre o universo Ticuna - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2000)
Magüta is the self-denomination of the Ticuna. The Magüta identity is related to the Ticuna universe and refers to the origin of the Ticuna people, before contact. The masks and mask garments from the Curt Nimuendaju Ethnographic Collection were taken as elements for the analysis of the Ticuna universe, and as ethnic artifacts referring to the Magüta identity. Ticuna is the identity "attributed" to the group after contact, which is established by relations of opposition. The relations of opposition between Ticuna and "whites" generate conditions for the (re)emergence of the Magüta identity. Complementary relations between Magüta/Ticuna identities can help to understand the resistance and adaptation of these Indians, creating strategies for the socio-cultural survival of the group.
From Ticuna to Magüta a study on the Ticuna universe
Keywords: Ticuna; Maguta; Curt Nimuendaju; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA